2016
DOI: 10.1016/j.recesp.2015.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Revisión sistemática de evaluaciones económicas de los sistemas de telemonitorización en los marcapasos

Abstract: Rev Esp Cardiol. 2016;69(2):125-133 Historia del artı´culo: Recibido el 9 de marzo de 2015 Aceptado el 8 de junio de 2015 On-line el 21 de octubre de 2015Palabras clave: Estudios de seguimiento Gasto cardiaco Marcapasos R E S U M E N Introduccio´n y objetivos: En la ú ltima dé cada, la telemedicina aplicada a la monitorizació n de marcapasos cardiacos ha experimentado un extraordinario crecimiento. Se desconoce si esta tecnología tiene una eficiencia diferente de la convencional. El objetivo del estudio es … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…This fact was reflected in the overload of informal caregivers. On the other hand, these results are similar to those obtained in previous studies that had assessed the economic impact of RM provided to patients with pacemakers [5,8,9,32,[34][35][36].…”
Section: Discussionsupporting
confidence: 89%
“…This fact was reflected in the overload of informal caregivers. On the other hand, these results are similar to those obtained in previous studies that had assessed the economic impact of RM provided to patients with pacemakers [5,8,9,32,[34][35][36].…”
Section: Discussionsupporting
confidence: 89%
“…A Cochrane review and a meta-analysis concluded that telemonitoring reduces all-cause mortality and HF-related hospitalisations [5,28]. Another systematic review reported that telemonitoring systems helped in the early detection of cardiovascular events compared to conventional monitoring, thus reducing the number of hospitalisations and hospital visits and lowering the costs associated with follow-ups [29].…”
Section: Discussionmentioning
confidence: 99%